(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
The purpose of this paper is to review some (pre-)historical assumptions beneath the classical Greek philosophy, that go back to the phrygian Great Mother, from which radiate over Minoan Crete, and reach continental Greece particularly through the institution of Eleusinian mysteries. The Great Goddess symbolizes an ontological, ethical and religious conception that has left its marks throughout the Mediterranean watershed, in elements such as the cavern, double-edged ax, butterfly-psyche, mystery initiation, sacramental renaissance, ecstatic dances, etc. Despite being savagely destroyed by the invasion of Indo-European patriarchy, such marks remain in the hidden substrate of hegemonic culture.